2008
DOI: 10.3763/aedm.2008.0076
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Perspectives on the Use of Virtual Reality within the Building Industries of Four Countries

Abstract: This paper presents results from the first stage of an analysis of the use of virtual reality (VR) within the building industries of strategically selected countries, namely, China, Sweden, the UK and the US. The aims of the research are to assess VR usage and its benefits within the building industries of these countries and to identify perceived barriers to VR usage and ways of overcoming them. The countries selected offer a range of experience in the adoption of VR technologies and the paper provides an ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Cumulative evidence has proved that VR is capable of providing a stronger sense of presence (Hoffman et al , 2003) and can replicate similar user behaviour as in the real-world (Heydarian et al , 2015). Through BIM, data visualisation can be supported by VR for the virtual representation of the FFE products within virtual or real spaces beyond 3D (Greenwood et al , 2008), which can address retrieving and presenting information and can increase efficiency on communication and problem-solving in an interactive and collaborative platform. This could aid the development of digital and virtual prototypes of FFE products that could be used to visualise and appraise designs by stakeholders as well as allow them the opportunity to evaluate alternatives before they are produced, built or incorporated into buildings (Cotey, 2017).…”
Section: The Relevance Of Immersive Technology and Building Information Modelling In The Furniture Fixture And Equipment Sectormentioning
confidence: 99%
“…Cumulative evidence has proved that VR is capable of providing a stronger sense of presence (Hoffman et al , 2003) and can replicate similar user behaviour as in the real-world (Heydarian et al , 2015). Through BIM, data visualisation can be supported by VR for the virtual representation of the FFE products within virtual or real spaces beyond 3D (Greenwood et al , 2008), which can address retrieving and presenting information and can increase efficiency on communication and problem-solving in an interactive and collaborative platform. This could aid the development of digital and virtual prototypes of FFE products that could be used to visualise and appraise designs by stakeholders as well as allow them the opportunity to evaluate alternatives before they are produced, built or incorporated into buildings (Cotey, 2017).…”
Section: The Relevance Of Immersive Technology and Building Information Modelling In The Furniture Fixture And Equipment Sectormentioning
confidence: 99%
“…If BIM is used with the VR technology, buildings and high-quality scenarios can be recreated, as demonstrated by Zaker et al [3], introducing people to an almost real world. Greenwood et al [13] demonstrated that it was advantageous to use BIM-VR to examine a building from different perspectives, as the approach improved the traditional visualization methods.…”
Section: Virtual Reality and Bimmentioning
confidence: 99%
“…These evolutions are referred to the terms of VR (Virtual reality), AR (Augmented Reality), and MR (Mixed Reality), generally bring together under the term XR for Extended Reality. However, their differences are not always clearly defined (Hanaoka et al 2018;Moore and Gheisari 2019;Greenwood et al 2008). In order to better understand the distinction, we refer on definitions formulated by Milgram and his colleagues (Milgram and Kishino 1994).…”
Section: The Implementation Of Immersive Technologies In Architecturementioning
confidence: 99%
“…Immersive technologies have been improved in terms of variety, display resolution, sensors accuracy and at the same time have become more affordable. Due to the successful implementation of these technologies across various sectors, including the aviation, medicine, military for example (Wang and Dunston 2007;Jeelani, Han, and Albert 2017;Krakhofer and Kaftan 2015), researchers have started to analyse the interest for the AEC industry (Greenwood et al 2008;Cheng, Chen, and Chen 2020). The interest for onsite applications (Billinghurst and Henrysson 2009), safety (Park et al 2015;Moore and Gheisari 2019), facility management (Shi et al 2016) have notably been demonstrated.…”
Section: Introductionmentioning
confidence: 99%